'They need our help': Non-governmental organizations and the subjectifying dynamics of the military as social cause. (April 2016) - Millar, Katharine M
The invasions of Iraq and Afghanistan spurred a range of popular activity – from anti-war protests to war boosterism to veterans' advocacy – purporting to 'support the troops'. Non-governmental organizations (NGOs), from veterans' welfare organizations to anti-war groups, are crucial to this transformation of 'the troops' into a social cause and matter of collective concern. As such, this article proposes an initial qualification of NGO representative practices as a form of media genre, characterized by striking similarity in presentation, structure and, particularly, explicitly normative tone. A poststructural discursive approach is utilized to examine the implications of this genre for the production of subjectivities and power relations inherent to 'supporting the troops' via a structured analysis of the public-produced texts of a selection of typologically identified NGOs in the US and the UK. The article goes on to highlight the ways in which NGO representations counterintuitively objectify those they seek to support, while simultaneously limiting the political possibilities of supporters. Overall, it is argued that within the context of the liberal state, the representations of support produced across the advocacy spectrum work to not only depoliticize conflict but to 'apoliticize' support for the troops as a matter of morality.